1986
DOI: 10.1177/073428298600400306
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Synthesis, Regulation, and Arithmetical Performance

Abstract: This study examined arithmetical performance in relation to Luria's theory of the functional organization of the brain and Das, Kirby, and Jarman's model of simultaneous-successive processes. It was found that both computation and problem solving are related to simultaneous synthesis and behavior regulation factors. However, tests of problem solving and quantitative ability loaded higher on the simultaneous synthesis factor than on the behavior regulation factor, while the computation test loaded higher on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
4

Year Published

1989
1989
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 11 publications
1
12
0
4
Order By: Relevance
“…This difference in scores seems to point to a cognitive weakness in simultaneous processing in the MLD group. This is consistent with the studies of relations between simultaneous processing and mathematical achievement (Garofalo, 1986;Leong et al, 1985;Naglieri & Das, 1987) and the interpretation of specific learning disabilities using theory-based multidimensional tests (Naglieri, 1999;Naglieri & Kaufman, 2001). A more rigorous possibility is to consider the mean score in successive processing as a cognitive weakness, so the difference between the MLD and LA groups could be considered a difference in coding, along the lines of research that establishes a direct link between simultaneous and successive processing and mathematical achievement (e.g., Deaño, 2000;Kroesbergen et al, 2010;Naglieri & Das, 1997a).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This difference in scores seems to point to a cognitive weakness in simultaneous processing in the MLD group. This is consistent with the studies of relations between simultaneous processing and mathematical achievement (Garofalo, 1986;Leong et al, 1985;Naglieri & Das, 1987) and the interpretation of specific learning disabilities using theory-based multidimensional tests (Naglieri, 1999;Naglieri & Kaufman, 2001). A more rigorous possibility is to consider the mean score in successive processing as a cognitive weakness, so the difference between the MLD and LA groups could be considered a difference in coding, along the lines of research that establishes a direct link between simultaneous and successive processing and mathematical achievement (e.g., Deaño, 2000;Kroesbergen et al, 2010;Naglieri & Das, 1997a).…”
Section: Discussionsupporting
confidence: 90%
“…In mathematics, the literature has reported relations between measures of mathematical achievement and the PASS cognitive processes (Das et al, 1994) simultaneous and successive processing (e.g., Garofalo, 1986;Kroesbergen et al, 2003;Kroesbergen, Van Luit, Naglieri, Taddei, & Franchi, 2010;Naglieri & Das, 1987), planning (e.g., Ashman & Das, 1980;Das & Heemsbergen, 1983;Garofalo, 1986;Joseph & Hunter, 2001;Kirby & Ashman, 1984), and attention (Kroesbergen et al, 2003;Warrick, 1989) and has concluded that successive processing correlates with mathematical performance, but generally at a lower level than simultaneous processing (Das, 1988;Garofalo, 1986;Leong, Cheng, & Das, 1985).…”
mentioning
confidence: 97%
“…This improvement means that the joint functioning of the three processes is necessary for mathematical improvement in children with low intelligence, using the PREP model. The correlational studies between mathematics and cognitive processes (Ashman & Das, 1980;Das et al, 1994;Garofalo, 1986;Iglesias-Sarmiento & Deañ o, 2011;Joseph & Hunter, 2001;Kirby & Ashman, 1984;Kroesbergen et al, 2003;Warrick, 1989) underscored the influence of a cognitive process in mathematical performance as a function of school grade. The empirical studies also justified the improvement of learning through the improvement of the promoted cognitive process Das et al, 1995;Naglieri & Gottling, 1995;Naglieri & Gottling, 1997;Naglieri & Johnson, 2000;Ramos et al, 2014).…”
Section: Discussionmentioning
confidence: 94%
“…The four cognitive components are differentially related to mathematical skills. The literature has reported relations between measures of mathematical achievement and the PASS cognitive processes (Das et al, 1994) simultaneous processing (Iglesias-Sarmiento & Deañ o, 2011), simultaneous and successive processing (Garofalo, 1986;Kroesbergen et al, 2010;Naglieri & Das, 1987), planning (Ashman & Das, 1980;Joseph & Hunter, 2001;Kirby & Ashman, 1984), and attention (Kroesbergen, Van Luit, & Naglieri, 2003;Warrick, 1989), concluding that successive processing correlates with mathematical performance, but generally at a lower level than simultaneous processing (Das, 1988;Leong, Cheng, & Das, 1985). These predictions are derived from the need of correct simultaneous processing to establish significant numerical units and to integrate them in higher-level numerical units, with one or more numbers, comprehension of the resulting numerical value, as well as of the statements of the verbal arithmetic problems.…”
Section: Pass Remedial Program Of Arithmeticmentioning
confidence: 98%
“…Research on planning has shown that this concept can be sufficiently operationalised to be measured, and that planning emerges as a factor distinct from coding. Simple tasks included activities such as Trail-Making, Visual Search, and Matching Numbers, whereas complex ones involved writing a story (Ashman & Das, 1980), solving syllogisms, Wisconsin Card Sorting Task (Garofalo, 1986), and inferring hidden codes. Das (1984), and Das and Dash (1983) have provided evidence that planning is different from and more than coding and information processing.…”
Section: The Pass Modelmentioning
confidence: 99%